The Effects of Carbon Monoxide and Lead Exposure on Lung Function: A Meta-Analysis - Yumanda, Anggie; Indi Esha (HM Publisher, 2024)
Background: Carbon monoxide (CO) and lead (Pb) are ubiquitous environmental pollutants with well-established detrimental health effects. The impact of these pollutants on lung function, a critical indicator of respiratory health, has been investigated in numerous studies. However, the findings have been inconsistent, necessitating a comprehensive meta-analysis to synthesize the evidence and provide a definitive assessment. Methods: A systematic search of electronic databases (PubMed, Scopus, Web of Science) was conducted to identify relevant studies published between 2018 and 2024. Studies investigating the association between CO and Pb exposure and lung function, measured by spirometry (Forced Expiratory Volume in 1 second [FEV1] and Forced Vital Capacity [FVC]), were included. A random-effects model was used to pool the effect estimates, and heterogeneity was assessed using the I² statistic. Results: The meta-analysis included 25 studies (n = 15,432 participants). The pooled results demonstrated a significant negative association between CO exposure and both FEV1 (standardized mean difference [SMD] = -0.32, 95% confidence interval [CI] = -0.45 to -0.19, p < 0.001) and FVC (SMD = -0.27, 95% CI = -0.38 to -0.16, p < 0.001). Similarly, Pb exposure was associated with a significant reduction in FEV1 (SMD = -0.21, 95% CI = -0.30 to -0.12, p < 0.001). The heterogeneity across studies was moderate to high (I² = 50-75%). Conclusion: This meta-analysis provides compelling evidence that both CO and Pb exposure are associated with impaired lung function. These findings underscore the importance of reducing exposure to these pollutants to protect respiratory health.